Indicadores de sustentabilidade do setor sucroalcooleiro: relações com as questões socioambientais - Silva, Ananda Islas da [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The society's demand for companies with environmental and social commitment forces the organizations to not only comply with the legislation. The benefits range from short and long term resource savings, the development of more sustainable technologies and profit generation. To this end it is necessary for the companies to effectively implement the concept of sustainability not only in its daily activities, but also in its business plans, in order to create a sustainable culture, conciliating profit and growth together with the proper management of resources, ensuring the contributors' well-being and safety. Therefore, this work aims to analyze, using sustainability reports, the main actions and sustainability indicators implemented in the sugar and alcohol sector as well in the energy sector. The results indicate the efforts in the reduction of the water consumption by the industry, investiments in inovation and technology, and workers' healthy and safety. The conclusion is that companies are seeking to go beyond legal compliance, in order to gain efficiency in processes and increase production without compromising the environment and ensuring employee safety

A demanda social por empresas que tenham boas práticas ambientais e sociais pressiona as organizações a ir além de simplesmente cumprir a legislação. Os benefícios vão desde a economia de recursos a curto e longo prazo ao desenvolvimento de novas tecnologias mais sustentáveis e a consequente geração de lucros. Para isso, é preciso que as companhias implementem efetivamente o conceito da sustentabilidade no seu dia a dia, no seu plano de negócios, criando uma cultura sustentável, isto é, conciliando lucro e crescimento da empresa junto com o manejo adequado de seus recursos, garantindo o bem estar e segurança dos colaboradores. O presente trabalho visa analisar, através de relatórios de sustentabilidade, quais são as principais condutas e indicadores de sustentabilidade implementados no setor sucroalcooleiro e energético. Os resultados obtidos indicam esforços na redução no consumo de água na indústria; investimentos em tecnologia e inovação e saúde e segurança dos trabalhadores. A conclusão é de que as empresas estão buscando ir além da conformidade legal, no intuito de ganhar eficiência nos processos e aumentar a produção sem comprometer o meio ambiente e garantindo a segurança dos colaboradores
Keywords: Energia - Fontes alternativas; Sustentabilidade; Sucroalcooleira; Sucroenergético; Energia; Indicadores ambientais; Cana-de-açúcar; Etanol